The Impact Of Covid-19 On The Pharmaceutical Industry: Lessons Learned And Future Outlook (Journal of Namibian Studies : History Politics Culture, 2023)
The COVID-19 pandemic has profoundly affected the pharmaceutical industry, reshaping priorities, accelerating innovation, and highlighting vulnerabilities in global healthcare systems. This article provides a comprehensive analysis of the impact of COVID-19 on the pharmaceutical sector, examining key lessons learned and offering insights into the future outlook. It explores the rapid development of vaccines and therapeutics, shifts in regulatory frameworks, supply chain disruptions, and changes in healthcare delivery models. Additionally, the article discusses the broader implications of the pandemic on drug discovery, clinical trials, digital health technologies, and collaboration within the industry. By synthesizing lessons from the pandemic response, this article aims to inform strategic planning and decision-making in the pharmaceutical industry as it navigates the post-pandemic landscape.